2009
DOI: 10.1146/annurev.earth.031208.100212
|View full text |Cite
|
Sign up to set email alerts
|

The Tectonic Framework of the Sumatran Subduction Zone

Abstract: The great Aceh-Andaman earthquake of December 26, 2004 and its tragic consequences brought the Sumatran region and its active tectonics into the world's focus. The plate tectonic setting of Sumatra has been as it is today for tens of millions of years, and catastrophic geologic events have likely been plentiful. The immaturity of our understanding of great earthquakes and other types of geologic hazards contributed to the surprise regarding the location of the 2004 earthquake. The timing, however, is probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
164
0
24

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(188 citation statements)
references
References 71 publications
0
164
0
24
Order By: Relevance
“…'%' is the percentage of sediments in the prism compared with total sediments. 18,19 ; the thickness of the accretionary wedge increases from 0.9 km (southeastern sector) to 4 km (northwestern sector) 9 following the direction of motion of the subducting plate; the presence of strong curvature of the trench could represent a limit for the lateral migration of sediments that accumulate in this area and increase the size of the accretionary wedge. The New Britain trench has little or no accretionary wedge to the east (thickness of the prism ¼ 0.1 km) but the thickness of the accretionary prism increases to the west, reaching 2.5 km (refs 4,9,10,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'%' is the percentage of sediments in the prism compared with total sediments. 18,19 ; the thickness of the accretionary wedge increases from 0.9 km (southeastern sector) to 4 km (northwestern sector) 9 following the direction of motion of the subducting plate; the presence of strong curvature of the trench could represent a limit for the lateral migration of sediments that accumulate in this area and increase the size of the accretionary wedge. The New Britain trench has little or no accretionary wedge to the east (thickness of the prism ¼ 0.1 km) but the thickness of the accretionary prism increases to the west, reaching 2.5 km (refs 4,9,10,20).…”
Section: Discussionmentioning
confidence: 99%
“…26). Low-viscosity and -density air and water layers (density ¼ 1 kg m À 3 , viscosity ¼ 10 19 Pa s) and sea water (density ¼ 1,000 kg m À 3 , viscosity ¼ 10 19 Pa s) at the top of the model simulate a free-surface-like condition for the crust; the solid portion of the model thus behaves as a free erosion/sedimentation surface 27 . Erosion and sedimentation are implemented in a highly simplified manner: sea level is set at 12 km from the top of the model, positive topography 44 km above the sea level is instantaneously eroded, trench is instantaneously filled by sediments at depths 48 km below the sea level.…”
Section: Methodsmentioning
confidence: 99%
“…They are the Eurasian Plate, the Australian Plate, the Indian Plate, the Sunda Plate, the Caroline Plate, the Philippine Sea Plate, and the Pacific Plate as shown in Fig. 1 (McCaffrey, 2009).…”
Section: F Febriani Et Al: Ultra Low Frequency (Ulf) Electromagnetimentioning
confidence: 99%
“…In these models, the Red River Fault (RRF) in northern Vietnam is regarded as the northeastern tectonic boundary between SC and SU accommodating right-lateral shear strain (Wilson et al, 1998;Michel et al, 2001;Kreemer et al, 2003;Simons et al, 2007). Meanwhile, Bird (2003) and McCaffrey (2009) suggested that this boundary is located farther south. Because of the slow relative motion between the SU and SC blocks and the scarcity of precise space geodetic measurements in this area, the actual location of the tectonic boundary is still uncertain.…”
Section: Introductionmentioning
confidence: 99%